An improved inflow turbulence generator for large eddy simulation evaluation of wind effects on tall buildings. Issue 1 (31st December 2023) - Deng, Ting; Chen, Zhiwei; Fu, Ji-Yang; Li, Yi
Abstract : Accurate inflow turbulence wind profile is a key premise of large eddy simulation (LES) methodology for super tall buildings. This paper presents an improved method for narrow band synthesis random flow generation to produce a more accurate inflow turbulence of LES based on superposition of harmonics. The proposed method considers time correlation by adopting time parameters, and an accurate expression of wind speed spectrum energy by a modified spectrum integral equation is used. These improvements could generate a more accurate turbulence intensity for the atmospheric boundary layer. A simple numerical example is applied to verify the spectrum characteristic, time correlation and spatial correlation of atmospheric numerical boundary layer. Meanwhile, the effects of the introduced parameters are investigated and the method is applied to the LES of the Commonwealth Advisory Aeronautical Research Council building (CAARC). The improved method could increase the accuracy of simulated turbulence intensity. Compared with the results of CAARC model obtained from the wind tunnel test, the improved method in this study decreases the errors of root-mean-square (rms) of the based bending moment from 5.3% to 4.1% in the along-wind direction and from 5.6% to 1.3% in the cross-wind direction.